An Evaluation of the Relationship between Perceived Stress and Breastfeeding Self-efficacy in Women Referred to Delivery Preparatory Classes in Zanjan, Iran in 2018 - Azizi E; Maleki A; Mazloomzadeh S; Pirzeh R (Preventive Care in Nursing and Midwifery Journal, 2018)
Background: Stress during pregnancy and delivery is associated with unfavorable outcomes, which negatively affects maternal breastfeeding self-efficacy. Objectives: This study aimed to determine the relationship between perceived stress and breastfeeding self-efficacy of women in Zanjan, Iran. Methods: This descriptive- analytical study was performed on 224 pregnant women, who participated in delivery preparation classes and were selected by Poisson random sampling. The data were collected using Demoghraphic and midwifery characteristics Questionnaires, Cohen’s perceived stress scale, and Dennis’s breast-feeding self-efficacy scale. In addition, data analysis was performed using descriptive statistics, Pearson’s correlation coefficient, and logistic regression model at 95% confidence interval. Results: In this study, the mean age of the participants was 26.56±4.61 years. Moreover, a majority of mothers were nulliparous (81.3%), had academic degrees (56.7%), and were housewives (86.6%). According to the results, there was a significant and reverse association between perceived stress and breastfeeding self-efficacy and neonatal weight at birth (P=0.0001) (P=0.01). While breastfeeding self-efficacy had a direct association with natural delivery, wanted pregnancy, neonatal weight, and family income level, It had a significant and reverse relationship with history of abortion (P<0.05). Conclusion: Due to the significant and negative relationship between perceived stress and self-efficacy as well as the importance of this issue in the rate of exclusive nutrition and continuation of lactation, planning to control perceived stress in nulliparous women with a history of abortion, unwanted pregnancy, and low income levels seems necessary.